A blind SLM receiver for PAR-reduced OFDM - Jayalath, A.D.S.; Tellambura, C. (Proceedings IEEE 56th Vehicular Technology Conference, 2002)
Selected mapping (SLM) generates a set of independent signals from an information sequence and transmits the signal with minimum peak-to-average power ratio (PAR). To recover data, the receiver is sent critical side information (SI) about the generation process. In this paper, a novel blind detection algorithm is developed for coded orthogonal frequency division multiplexing (OFDM) and SLM. The blind SLM algorithm performs well in both AWGN and fading channels in the presence of amplifier non-linearities.